The effects of radiative cooling on oscillating coronal loops - Mendoza Briceño, César; Luna Cardozo, Marialejandra (Ciencia)
Recently, high resolution observations by SOHO and TRACE spacecraft have identified oscillating loops and propagating waves in the solar coronal. These new discoveries established a new discipline that is known as coronal seismology. The importance of this lies in the potential for the diagnostics of coronal structures and knowledge of coronal heating. We present a study of the effects of radiative cooling and heating processes on longitudinal waves in coronal loops. We find that radiation and heating results in a modification in the evolution of temperature and pressure perturbations but not in the decay time of the wave.